2015
DOI: 10.1111/jmi.12330
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of structural changes in acute inflammation by fractal dimension, angular second moment and correlation

Abstract: The aim of the study was to examine alteration and possible application of fractal dimension, angular second moment, and correlation for quantification of structural changes in acutely inflamed tissue. Acute inflammation was induced by injection of turpentine oil into the right and left hind limb muscles of mice, whereas control animals received intramuscular saline injection. After 12 h, animals were anesthetised and treated muscles collected. The tissue was stained by hematoxylin and eosin, digital micrograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
(35 reference statements)
2
14
0
Order By: Relevance
“…TMT decreases ENT values suggesting that overall increase in AMPase activity made tissue more homogeneous due to increase in expression and/or activity of eN in both glial cells and remaining synapses. Furthermore, post-intoxication increase in COR values corroborates image homogeneity due to increase in AMPase activity on synapses and glial cells, as COR measures gray-linear dependency of adjacent pixels (Stankovic et al, 2016). ROC analysis demonstrated high discriminatory power of GLCM parameters (Metz, 1978; Zweig & Campbell, 1993; Pantic et al, 2014), but since two analyzed regions have different patterns of AMPase activity we postulate that CON and INV are especially useful in analyzing this type of enzyme histochemistry.…”
Section: Discussionmentioning
confidence: 77%
“…TMT decreases ENT values suggesting that overall increase in AMPase activity made tissue more homogeneous due to increase in expression and/or activity of eN in both glial cells and remaining synapses. Furthermore, post-intoxication increase in COR values corroborates image homogeneity due to increase in AMPase activity on synapses and glial cells, as COR measures gray-linear dependency of adjacent pixels (Stankovic et al, 2016). ROC analysis demonstrated high discriminatory power of GLCM parameters (Metz, 1978; Zweig & Campbell, 1993; Pantic et al, 2014), but since two analyzed regions have different patterns of AMPase activity we postulate that CON and INV are especially useful in analyzing this type of enzyme histochemistry.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, the overall morphologic complexity is measured by the fractal dimension (Bizzarri et al, 2011 ). Biological systems have been studied under the fractal perspective (Copley et al, 2012 ; Wedman et al, 2015 ; Lennon et al, 2016 ; Stankovic et al, 2016 ). There are reports suggesting that the fractal dimension discriminates between healthy and pathological conditions (Hiroshima et al, 2016 ; Zehani et al, 2016 ; Müller et al, 2017 ; Zhang et al, 2017 ; Popovic et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, IDM relates inversely to CON, while ASM is an opposite of ENT. COR measures the grey-linear dependency of neighboring pixels, where high COR indicates greater pixel similarity and low COR points towards irregularity in image texture [37]. Our results showed that nuclei of SA-β-Gal + cells, have higher values of ENT and CON than SA-β-Gal -cells, while ASM, IDM and COR of cell nuclei are higher in the SA-β-Gal -group.…”
Section: Discussionmentioning
confidence: 61%